Exergy analysis of a biorefinery process for co-production of third-generation L-lactic acid and electricity from Eucheuma denticulatum residues - Chung, M.R.W.Y. (Elsevier Ltd, 2022)
This paper evaluates the thermodynamic performance of three different l-lactic acid (LLA) biorefinery scenarios, utilizing macroalgae cellulosic residue, namely Eucheuma denticulatum residues (EDRs), as raw materials. To establish exergy analysis, the thermodynamic properties of each biorefinery scenario was obtained through process simulation using Aspen PlusÂ® V10. It was found that microwave-assisted autohydrolysis (MAA) was feasible in minimizing the amount of EDRs needed by 70.2 to produce 1000 kg/h of LLA. The fermentation unit, wastewater treatment (WWT) unit, and combined heat and power (CHP) unit were ranked top three for the occurrence of exergy destruction. Both the LLA recovery unit (99.37) and MAA pretreatment unit (99.68) were found to be highly exergetically efficient. Among the three scenarios, Scenario III, which was integrated with power generation and a proper waste management system, had the highest functional exergy efficiency (22.12) and normalized exergy destruction (0.73). It demonstrated the highest functionality due to the prevention of material losses by converting waste streams into value-added products and reducing reliance on fossil-fuel derived energy for plant operation. The valuable information from exergy analysis provides theoretical guidance for performance enhancement in a macroalgae-based biorefinery to produce LLA, either with process integration or technology advancement. Â© 2021 Elsevier Ltd